Thermal regime, together with lateral connectivity, control aquatic invertebrate composition in river floodplains. (26th July 2022) - Marle, Pierre; Riquier, Jérémie; Timoner, Pablo; Mayor, Hélène; Slaveykova, Vera I.; Castella, Emmanuel
Abstract: Large river floodplains are dynamic environments, where alternating low and high flows are key ecological processes shaping aquatic biota. As a result of fluctuations in flow in floodplain channels, the diversity of benthic assemblages is assumed to result from the balance between surface flow connections, which are dominant during high flows, and groundwater inputs, which are dominant during low flows. However, the relative importance of these inputs in explaining aquatic invertebrate diversity has never been tested. The response of aquatic invertebrates to hydrological changes of a river floodplain was investigated in seven braided and six braided–anastomosed floodplain channels of the French upper Rhône River that are fed by three different processes: groundwater supply (which controls the thermal inertia of the water bodies), surface slow flow connections (i.e. diffuse overbank flows; passive overflow), and surface shear stress‐related connections (i.e. condensed flows; active overflow) during high flows. Generalised dissimilarity models indicated that floodplain invertebrate composition had complex relationships with the three processes considered. The relative importance of the latter appeared dependent upon the morphology of the floodplain channels. In the braided channels, the effects of shear stress‐related connections were more prominent than in the anastomosed ones, for which the effects of the three processes were more similar. Overall, the diversity of flow connections, that is, lateral surface water connections (both shear stress‐related and slow, as defined above) and vertical connection with groundwater (inferred through thermal inertia) enhanced the species turnover at the reach scale. Thermal inertia influenced invertebrate composition when, during low flow periods, surface flow connections had limited effect. Our results highlighted that the role of hydrologic connectivity upon floodplain diversity cannot be reduced to a single process. They also indicate the importance of vertical connectivity for maintaining biodiversity in floodplain habitats where surface flow connectivity is neither frequent nor constant.